POLA KEPEMIMPINAN SISWA DALAM DISKUSI KELOMPOK KECIL PADA PEMBELAJARAN MATEMATIKA DI KELAS V SD - Mita Oktavy; Siti Afifah Siregar; Nurhasannah; Darling Krisman Zega; Winara; Ibrahim Gultom (STKIP Subang, 2026)
This study aims to describe the patterns of student leadership in small group discussions during mathematics learning in Class V of SD Ulun Nuha, Medan. This research uses a qualitative descriptive approach with a case study design. Data were collected through pre-observation interviews with the classroom teacher and structured observation using a checklist instrument covering eight aspects: discussion opening phase, leadership initiation, decision making, verbal communication, conflict management, member motivation, summarizing and reporting, and general leadership patterns. The observation was conducted on six groups of students during a mathematics lesson on whole numbers up to 1,000,000. Results show four distinct leadership patterns: centralized leadership (T), rotating leadership (B), collective/deliberative leadership (K), and no clear leadership (TP). The most dominant pattern is centralized leadership, appearing in two groups. Academic ability was found to be the most consistent factor influencing leadership emergence across all groups, while social factors such as gender also played a role in several groups. These findings suggest that student leadership in mathematics group discussions is diverse and largely informal, highlighting the need for teachers to deliberately scaffold leadership skills as part of collaborative learning.